(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Giardiasis (lyambliosis), caused by the protozoan parasite Giardia duodenalis, remains a global public health concern, particularly within developing nations and regions with specific environmental profiles. The persistent colonization of the upper small intestine by Giardia trophozoites leads to the destruction of the mucosal brush border, triggering malabsorption syndrome and chronic enteropathy. Emerging clinical evidence indicates that this pathophysiological cascade significantly impairs the homeostasis of essential micronutrients. Chronic giardiasis alters the systemic balance of vital trace elements such as Zinc (Zn), Copper (Cu), Iron (Fe), and Selenium (Se) which serve as critical cofactors for enzymatic antioxidant defense and immune cell proliferation.